The Element "Use of Narcotic or Analogue Drugs" under Art. 343b (3) Criminal Code of the Republic of Bulgaria - Petkova, Sylvia (Law Journal of New Bulgarian University, 2024)
The study focuses on the theoretical and practical problems that arise from the formulation "after use of narcotic or analogue drugs" as a main objective characteristic of the crime under Article 343b(3) of the Criminal Code of the Republic of Bulgaria. It is argued that the driving of a motor vehicle in the formal presence of this characteristic does not always constitute an act of a high degree of public danger. That argument is because public danger is created by the driving of a motor vehicle by a driver who is unable to carry out that activity properly and safely because of the use of narcotic or analogue drugs. In that connection, the content of the concepts of "after the use" of narcotic or analogue drugs and "under the influence" of such substances is examined, a distinction being drawn between them on the basis of the science of "toxicology" as a source of the special knowledge required. A number of hypotheses are reviewed. It is argued that under those hypotheses the application of Article 9(2) of the Criminal Code of the Republic of Bulgaria on the insignificance or the obvious insignificance of driving a motor vehicle after the use of narcotic drugs or their analogues may be considered.